Analisis Perbandingan Kuat Tekan dan Kuat Tarik Beton SCC dengan Campuran Pasir Cilopang dan Pasir Cimalaka - Aditia Saparingga; Dendi Yogaswara (Jurnal Konstruksi, 2023)
Concrete has different compressive strength and tensile strength depending on the mixture of fine aggregate and coarse aggregate used. The use of SCC concrete mixed with Cilopang sand and SCC concrete mixed with Cimalaka sand has different compressive and tensile strengths. The purpose of this study was to determine the ratio of the compressive strength and tensile strength of SCC concrete with a mixture of Cilopang sand and Cimalaka sand. The method used in this study was an experiment or experiment in the laboratory, namely by conducting an experiment on a number of test objects to compare SCC concrete with a mixture of Cilopang sand with the addition of Superplasticizer and SCC concrete with Cimalaka sand with the addition of Superplasticizer. The total samples were 12 cylindrical concrete samples with dimensions of 150 mm x 300 mm with a percentage of liquid superplasticizer mixture of 1.8% of the total volume of fine aggregate (sand) with a concrete age of 7, 14 and 28 days. SCC concrete with a mixture of Cilopang sand in 6 samples and SCC concrete with a mixture of Cimalaka sand in 6 samples. It can be concluded from SCC concrete aged 28 days with a mixture of Cilopang sand for a compressive strength of 26.07 MPa and a tensile strength of 3.027 MPa. And SCC concrete with a mixture of Cimalaka sand for a compressive strength of 23.21 MPa and a tensile strength of 2.708 MPa. Based on the results of the two compression tests and tensile tests that have been carried out, it shows that SCC concrete mixed with Cilopang sand is superior to SCC concrete mixed with Cimalaka sand.